Stufflebeam's Model Application of Education Management Information Systems (EMIS) in Improving the Quality of Learning Services - Heri Kuswara; Engkus Kuswarno; Ahmad Mudrikah; Usep Kosasih (Nidhomul Haq : Jurnal Manajemen Pendidikan Islam, 2021)
Advances in science and information technology have changed the perspective and lifestyle of the Indonesian people in carrying out their activities, including in the world of education. The application of the Education Management Information System (Emis) today is a must for every educational institution. In learning, the application of Emis is expected to improve the quality of learning services which in turn will improve the quality of teachers and students, especially in the field of Information Technology. The four basic management functions put forward by Terry are Planning, Organizing, Actuating and Controlling (POAC), the dimensions of service quality created by Haksever et al., As well as the program evaluation model developed by Stufflebeam (Stufflebeam's Model) or CIPP Model, Becomes theoretical basis as an analysis knife or the framework of ideas used to analyze, synthesize and provide solutions for the application of Emis in SMA and SMK Ma'arif Banyuresmi Garut in improving the quality of learning services. The implementation of Emis in SMA and SMK Ma'arif starts with the creation of a strategic plan for learning Emis, the formation of an IT team and a letter of assignment, budget provision, preparation and procurement of learning media for Emis, preparation of Standard Operating Procedures (SOP), socialization and training on the use of Learning Emis, Implementation of Learning Emis, Evaluation of the application of Learning Emis and the impact of the application of Learning Emis on the quality of learning services and on the quality of teacher human resources and the quality of student human resources